SOCIALIZATION OF PHASE B FITNESS TEST MEASUREMENTS FOR INDONESIAN STUDENTS AT UPT SPF SD NEGERI PANNARA MAKASSAR - Aprilo, Ians (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
This outreach activity aims to introduce the Phase B Indonesian Student Fitness Test (TKSI) which has not been carried out much for elementary school students. The subjects of this activity were students in grades 3 and 4 of UPT SPF at Pannara State Elementary School, Makassar, totaling 26 children. The test in TKSI Phase B includes 5 test items, namely the V Sit and Reach Test, Half Up Test, Hand-Eye Coordination Test, T-Test, and Around The World Test. The results of this socialization were 2 or 7.7% of students in the very good category, in the good category there were 23 or 88.5% of students and in the medium category only 1 student or 3.8%. So it can be categorized that the physical fitness level of students in grades three and four of UPT SPF SD Negeri Pannara Makassar is in the good category.